Penerapan Snort Sebagai Sistem Pendeteksi Serangan Keamanan Jaringan - Dasmen, Rahmat Novrianda; Ariyanto, Cendri; Surya, Muhammad Haris; Ramadhan, Hafiizh (STIKOM Tunas Bangsa Pematangsiantar, 2022)
Network security is very important in an effort to prevent abuse on a network.Our research aims to detect networks using snort where this application has sensor that can indentify abuse on the network besides snort also funcitions to detect intrusions. Detection is carried out according to the rules contained in the configuration file,snort can perform analysis on rule based systems,adaptive system.Snort can operate sniffer mode, packet logger mode and intrusion detection mode